Evaluasi Desain UI pada Prototype Aplikasi Influencer Marketing Endorsfy dengan Metode SEQ - Anak Agung Ngurah Mahadana Apta Gotra; Anak Agung Istri Ngurah Eka Karyawati (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
The success of a digital product relies heavily on the inseparable relationship between User Interface (UI) and User Experience (UX). Although UI is a fundamental aspect of UX, it's imperative to acknowledge that the UI's design, functionality, and ease of use are pivotal factors that can make or break a digital product's success. A top-notch UI design can significantly enhance the UX, while a deficient and convoluted UI can lead to a less-than-stellar user experience. In this study, we undertake the task of evaluating the UI quality of